Knowledge, attitude and practice related to diabetes mellitus among the general public in Galle district in Southern Sri Lanka: a pilot study - Herath, H. M. M; Weerasinghe, N. P.; Dias, H.; Weerarathna, T. P. (BMC public health, 2017)
Background Type 2 diabetes mellitus (DM) has become a global epidemic with significant disability and premature death. Identification of the level of knowledge, attitude and practice (KAP) related to diabetes among the general public is important in strategies for prevention of diabetes mellitus. Methods This study was conducted as a community based cross sectional study in three Medical Officers of Health (MOH) areas in Galle district. Previously healthy literate individuals who have not attended any diabetes education program in the last two years were selected for this study. Results A total of 277 participants were included in the study. The majority (77%) had either moderate (39%) or above moderate knowledge (38%) on diabetes mellitus. Even though, level of education was significantly and positively associated with knowledge ( p = 0.001), the association of gender and age with knowledge was not significant. Unlike knowledge, the attitude towards diabetes was poor in majority (90%) and level of education had no significant effect on attitude. With regards to practices, more than half of study subjects never had their blood sugar checked and, about 65% used to take refined sugar liberally and a large majority (80%) had no regular exercise activity. Conclusions Even though the majority (77%) had moderate or above moderate knowledge on diabetes, their attitudes towards diabetes was poor (88%). It appears that the higher knowledge on diabetes did not translate into good practices as over 50% of study subjects did not involve with any preventive measures. Therefore, more emphasis should be given to address the issue of poor attitude and practices towards diabetes mellitus among general public in Sri Lanka.